(3QSGdI aj JMbjb ePgH GdUhajI hGdeJcdejf hGdMceGA GdeJbOejf hJbQjQ bhdge aj hLhO GdhGLH dPGJgs
(3ChdgG (B:s
(3GdMeO ddg GdPi JLdi HPGJg dPGJg CeG HYO gPg QSGdg ai JMbjb ePgH GdUhajI Ef ai GdhLhO hGLHkG s
(3BNQgG (B:s
(3JMbbJ GdfSH GdEjLGHjI ddPGJ GdEdgjI hGdMbGFb GdchfjI ai eQJHI GdYde GdEdgi ceG PgH Edjg GdUhajI GdehMOI JeJ hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9276) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs